Physics-Aware AI-Initialized Dynamical Downscaling for Regional Extreme-Weather Forecasting with Open Climate Data - Mina Annetta; Shanti Purohit; Viljar Vagle; Deepak Deo (Jejaring Penelitian dan Pengabdian Masyarakat, 2026)
Accurate regional forecasting of extreme precipitation remains difficult because the scales that control disaster-producing rainfall are neither fully resolved by global numerical weather prediction nor reliably preserved by current global artificial intelligence weather models. Global AI systems such as Pangu-Weather, GraphCast, GenCast, and related models have transformed medium-range forecasting skill and computational efficiency, yet they remain fundamentally constrained by coarse training targets, regression-induced smoothing, and limited direct representation of terrain-locked convection and local hydrometeorological extremes. This paper reconstructs and substantially extends an event-based manuscript on AI-driven regional forecasting into a submission-oriented framework centered on the more defensible idea of physics-aware regional extreme-weather forecasting or downscaling with open climate data. The core argument is that AI should not be treated as a wholesale substitute for high-resolution regional physics; rather, it should be used as a skillful large-scale predictor whose state can be physically harmonized and injected into a regional nonhydrostatic model. We therefore formalize an AI-initialized, physics-aware dynamical downscaling pipeline in which open global reanalysis and observation products are used to generate, constrain, and evaluate regional forecasts of extreme rainfall. The framework is instantiated using the published North China July–August 2023 extreme precipitation case, for which the original study compared WRF simulations driven by Pangu forecasts against WRF simulations driven by NCEP GFS forecasts across lead times of 0.5, 3.0, and 5.5 days. This paper contributes in three ways. First, it repositions the original study within the modern literature on AI weather forecasting, regional downscaling, and physically constrained machine learning. Second, it formulates the coupling problem mathematically, clarifies the state alignment needed to make AI forecasts dynamically usable by WRF, and introduces a coherent reliability-oriented evaluation logic based on error growth, threshold skill, and event-structure consistency. Third, it reorganizes the experiments and results into a rigorous narrative grounded in reproducibility. Using the published event-level metrics, the AI-initialized regional system outperforms the GFS-initialized counterpart at extended lead times. For the North China case, the maximum precipitation threshold retaining a Threat Score of at least 0.1 is 400 mm at 5.5-day lead for Pangu-initialized WRF, whereas the GFS-driven counterpart retains comparable skill only at 50 mm. At 0.5-day lead, both systems perform competitively, but the AI-driven system still exhibits stronger spatial correlation (0.76 versus 0.68) and lower RMSE (86.2 mm versus 96.4 mm). The evidence supports a restrained but important conclusion: physics-aware AI-initialized regional modeling is a promising route for long-lead extreme-weather forecasting, yet current evidence remains case-limited and should be interpreted as a strong event-based demonstration rather than universal proof of general superiority.